2002
DOI: 10.1046/j.1365-246x.2002.01564.x
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of first-order backscattered P and S waves for time-lapse seismic imaging in heterogeneous reservoirs

Abstract: Summary First‐order elastic wave scattering theory, validated in general features by deep‐borehole seismic coda wave observations, is used to numerically simulate time‐lapse borehole seismic data aimed at monitoring oil–water substitution in heterogeneous hydrocarbon reservoirs. A first‐order perturbation solution of the vector wave equation leads to P–P and S–S backscattered displacement vector motion expressed as the angular summation of the second radial derivative of P‐ and S‐wave velocity and density fluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…The technology of seasonal gas storage in reservoirs suggests the potential for gas injection into aquifers as a means of providing target volumes for suitably low-cost, highresolution time-lapse seismic imaging (Leary 2002;Yuh & Gibson 2001). However, the cost of well infrastructure similar to that deployable at candidate waste disposal sites could be better justified if the power-law-scaling complexity of geofluid reservoirs were more widely and comprehensively understood.…”
Section: O N C L U S I O N Smentioning
confidence: 99%
See 1 more Smart Citation
“…The technology of seasonal gas storage in reservoirs suggests the potential for gas injection into aquifers as a means of providing target volumes for suitably low-cost, highresolution time-lapse seismic imaging (Leary 2002;Yuh & Gibson 2001). However, the cost of well infrastructure similar to that deployable at candidate waste disposal sites could be better justified if the power-law-scaling complexity of geofluid reservoirs were more widely and comprehensively understood.…”
Section: O N C L U S I O N Smentioning
confidence: 99%
“…In analogy with neutron and optical scattering data for ferromagnetic and opalescent fluid fixtures, Leary (2002) showed that the temporal spectra of seismic coda waves recorded deep in crustal rock (Leary & Abercrombie 1994a,b) are explained by seismic scattering in 1/k-scaling spatial fluctuations of elastic parameters recorded in a deep crustal well in crustal granites (Leary 1991). The concept of infinite correlation length for crustal rock percolation systems yields the power-law-scaling correlation function x(r)3r x2 and its frequency-domain dual the Fourier power spectrum S(k)31/k appropriate for crustal rock.…”
mentioning
confidence: 99%
“…Leary (2002) used first‐order elastic wave scattering theory to numerically simulate time‐lapse borehole seismic data aimed at monitoring oil–water substitution in heterogeneous hydrocarbon reservoirs. In his work, P ‐wave backscatter ‘snapshots’ of a heterogeneous rock can be acquired with a borehole seismic source and sensor located at the centre of the volume.…”
Section: Introductionmentioning
confidence: 99%
“…Leary, 2002;Sarkar et al, 2003). The characterization of the depletion process in a producing hydrocarbon reservoir is of importance for both fluid injection strategies (e.g.…”
Section: Introductionmentioning
confidence: 99%